Идентификация трудноизвлекаемых запасов нефти Югры; Геофизический журнал; Т. 41, № 4 - Кузьменков С. Г. Станислав Григорьевич; Кузьмин Ю. А. Юрий Алексеевич; Стулов П. А. Пётр Александрович; Аюпов Р. Ш. Роман Шамильевич; Булатов В. И. Валерий Иванович; Игенбаева Н. О. Наталья Олеговна; Исаев В. И. Валерий Иванович; Лобова Г. А. Галина Анатольевна (2019, 2019)
Заглавие с экрана